BOJONEGORO'S ECONOMIC GROWTH STRATEGY: TURNING CURSES INTO BLESSINGS - Suyoto, Suyoto; Adi, Fery Permana (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2021)
The purpose of this study is to analyze the economic dan resources growth in Bojonegoro using six pillars sustainble development in order to improve it's human capital and capital resources. This study was conducted in Bojonegoro, using qualititave approach with the level of explanation descriptive. As for the type of data used in this research included in this type of qualitative data. Data collection techniques used self inqury secondary data analysis include, observation and documentation. The data analysis technique used in this research is a descriptive technique which includes three stages of analysis, namely data reduction, data display and conclusion drawing/verification. The result show that in general, the six pillars of Bojonegoro's sustainable development as stated in the previous discussion are basically the choice of the path of transformation, but it is still necessary to confirm how this scenario will be followed. For this, it is necessary to affirm what must be transformed, namely the six elements of Bojonegoro's transformation, Vision Transformation, Vision for Economic Development, Environmental Vision, Social Vision, Fiscal Policy Vision,Vision of the Bureaucracy, Vision of Leadership